2019
DOI: 10.14449/jbd.2019.7.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mastocheck for Screening of Early Breast Cancer: Comparison with Screening Mammography

Abstract: This study was designed to verify the effectiveness of Mastocheck, a new diagnostic tool developed with proteomics techniques using plasma proteins. In addition, checked the current state of mammography used for breast cancer screening. Methods: A total of 305 cases were analyzed (normal 122, breast cancer 183) and used for validation after Mastocheck development. First, screening mammograms of normal patients and pre-diagnosis mammography of cancer patients were reviewed retrospectively. The results were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
11
2
Order By: Relevance
“…In recent times, the use of multiple markers for BC detection is gaining interest because, the combination of functionally important genes and proteins involved in breast tumorigenesis, have exhibited better diagnostic accuracy than single candidate markers 30 . A 3-protein diagnostic model named Mastocheck was able to predict BC with a sensitivity, specificity of 71.58%, 85.25% and AUC 0.8323 39 , 40 . A tumour suppressor methylation panel ( APC, BIN1, BMP6, BRCA1, CST6, ESR-b, GSTP1, P16, P21 and TIMP3 ) showed 91.7% sensitivity in distinguishing BC patients from normal individuals 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, the use of multiple markers for BC detection is gaining interest because, the combination of functionally important genes and proteins involved in breast tumorigenesis, have exhibited better diagnostic accuracy than single candidate markers 30 . A 3-protein diagnostic model named Mastocheck was able to predict BC with a sensitivity, specificity of 71.58%, 85.25% and AUC 0.8323 39 , 40 . A tumour suppressor methylation panel ( APC, BIN1, BMP6, BRCA1, CST6, ESR-b, GSTP1, P16, P21 and TIMP3 ) showed 91.7% sensitivity in distinguishing BC patients from normal individuals 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported 0.0668 as an optimal cut-off value of Mastocheck® for breast cancer diagnosis, with a sensitivity and speci city of 67.0% and 82.0%, respectively. Further validation studies showed sensitivity and speci city of 71.6% and 85.3%, respectively, with the cut-off value mentioned above (31,32). Based on this, a positive result was de ned as a Mastocheck® value of ≥ 0.0668 and a negative result of < 0.0668 [32].…”
Section: Preparation Of Blood Samplesmentioning
confidence: 97%
“…Further validation studies showed sensitivity and speci city of 71.6% and 85.3%, respectively, with the cut-off value mentioned above (31,32). Based on this, a positive result was de ned as a Mastocheck® value of ≥ 0.0668 and a negative result of < 0.0668 [32].…”
Section: Preparation Of Blood Samplesmentioning
confidence: 97%
See 2 more Smart Citations